Analisa Faktor – Faktor Yang Mempengaruhi Likuditas Pada Perusahaan Manufaktur Di Sektor Industri Barang Konsumsi Tahun 2007-2011 - Devona Theodora (Business Accounting Review, 2013)
This study aimed to determine the factors that affected the liquidity in the manufacturing sector of the consumer goods industry. This study used one dependent variable that was liquidity and 3 independent variables which were namely firm size, debt ratio and inventory turnover. The sample used in this study was a manufacturing company in the consumer goods industry from 2007 to 2011. The hypothesis tested by using multiple linear regression models. The results of this study showed that the company size had a significant positive effect on liquidity. While debt ratio and inventory turnover had a significant negative effect on liquidity.